Side readout of long scintillation crystal elements with digital SiPM for TOF‐DOI PET - Yeom, Jung Yeol; Vinke, Ruud; Levin, Craig S. (Medical physics (Lancaster), 2014)
Purpose: Side readout of scintillation light from crystal elements in positron emission tomography (PET) is an alternative to conventional end‐readout configurations, with the benefit of being able to provide accurate depth‐of‐interaction (DOI) information and good energy resolution while achieving excellent timing resolution required for time‐of‐flight PET. This paper explores different readout geometries of scintillation crystal elements with the goal of achieving a detector that simultaneously achieves excellent timing resolution, energy resolution, spatial resolution, and photon sensitivity. Methods: The performance of discrete LYSO scintillation elements of different lengths read out from the end/side with digital silicon photomultipliers (dSiPMs) has been assessed. Results: Compared to 3 × 3 × 20 mm3 LYSO crystals read out from their ends with a coincidence resolving time (CRT) of 162 ± 6 ps FWHM and saturated energy spectra, a side‐readout configuration achieved an excellent CRT of 144 ± 2 ps FWHM after correcting for timing skews within the dSiPM and an energy resolution of 11.8% ± 0.2% without requiring energy saturation correction. Using a maximum likelihood estimation method on individual dSiPM pixel response that corresponds to different 511 keV photon interaction positions, the DOI resolution of this 3 × 3 × 20 mm3 crystal side‐readout configuration was computed to be 0.8 mm FWHM with negligible artifacts at the crystal ends. On the other hand, with smaller 3 × 3 × 5 mm3 LYSO crystals that can also be tiled/stacked to provide DOI information, a timing resolution of 134 ± 6 ps was attained but produced highly saturated energy spectra. Conclusions: The energy, timing, and DOI resolution information extracted from the side of long scintillation crystal elements coupled to dSiPM have been acquired for the first time. The authors conclude in this proof of concept study that such detector configuration has the potential to enable outstanding detector performance in terms of timing, energy, and DOI resolution.